2016
DOI: 10.1021/acschemneuro.6b00087
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Prefrontal Inactivation Results in Reversed Dopaminergic Responses in the Shell Subregion of the Nucleus Accumbens to NMDA Antagonists

Abstract: Striatal dopaminergic dysregulation in schizophrenia could result from a prefronto-striatal dysconnectivity, of neurodevelopmental origin, involving N-methyl-d-aspartate (NMDA) receptors. The dorsomedian shell part of the nucleus accumbens is a striatal subregion of particular interest inasmuch as it has been described as the common target region for antipsychotics. Moreover, NMDA receptors located on the dopaminergic endings have been reported in the shell. The present study examines in adult rats the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 55 publications
(100 reference statements)
10
10
0
Order By: Relevance
“…Interestingly, no differences were observed in locomotor activity in the period preceding the injection between the animals microinjected with PBS or TTX within the SUB, suggesting that the SUB neonatal inactivation has no significant impact on basal locomotor activity. As regards the animals microinjected with PBS in the SUB, the profile of the ketamine-induced responses, and in particular the marked response lasting about 50min for the 20 mg/kg sc ketamine dose, is consistent with the variations previously reported after neonatal injection of PBS in the prefrontal cortex (Usun et al, 2013;Pouvreau et al, 2016). In animals subjected to the neonatal TTX blockade of the SUB at PND8, ketamine-induced locomotor responses were more elevated and more durable for the two higher doses (10 mg/kg sc and 20 mg/ kg sc), and in a significant way (compared to PBS animals) for the 20 mg/kg sc dose.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, no differences were observed in locomotor activity in the period preceding the injection between the animals microinjected with PBS or TTX within the SUB, suggesting that the SUB neonatal inactivation has no significant impact on basal locomotor activity. As regards the animals microinjected with PBS in the SUB, the profile of the ketamine-induced responses, and in particular the marked response lasting about 50min for the 20 mg/kg sc ketamine dose, is consistent with the variations previously reported after neonatal injection of PBS in the prefrontal cortex (Usun et al, 2013;Pouvreau et al, 2016). In animals subjected to the neonatal TTX blockade of the SUB at PND8, ketamine-induced locomotor responses were more elevated and more durable for the two higher doses (10 mg/kg sc and 20 mg/ kg sc), and in a significant way (compared to PBS animals) for the 20 mg/kg sc dose.…”
Section: Discussionsupporting
confidence: 88%
“…H. SAOUD et al Neurochemistry International xxx (xxxx) xxx-xxx motor hyperactivity observed in the present work is similar to the ketamine-induced locomotor responses observed after neonatal inactivation of the prefrontal cortex (Usun et al, 2013;Pouvreau et al, 2016), although not identical, inasmuch as maximum locomotor increases observed after neonatal SUB functional blockade with the 20 mg/kg sc ketamine dose appeared to be delayed in time. The reasons for that difference are yet to be determined.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast, cariprazine and aripiprazole are partial agonists at dopamine D 2 and D 3 receptors and serotonin 5-HT 1A receptors and antagonists at 5-HT 2A receptors (Kiss et al 2010 ). Importantly, alterations in glutamate transmission can impact dopamine levels, as NMDA receptor antagonism results in aberrant dopamine transmission (Adams et al 2002 ; Kapur and Seeman 2002 ; Pouvreau et al 2016 ). Moreover, NMDA antagonism induces upregulation of striatal dopamine D 2 receptors (Nair et al 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…The DAergic increases observed in the animals microinjected with PBS in the SUB are compatible with the results of the metaanalysis published by Kokkinou et al (2018) regarding the Nacc as a whole. In this respect, it is tempting to suggest that the high heterogeneity observed in the meta-analysis (Kokkinou et al, 2018) may have to do with opposite ketamine-induced DAergic variations in the shell and core subareas of the Nacc, inasmuch as such opposite variations have been observed in the two subregions after treatment with another non-specific NMDA antagonist, MK-801 (Pouvreau et al, 2016;Tagliabue et al, 2017), and no differential regional analyses have been carried out in the other studies (Kokkinou et al, 2018). In animals microinjected with TTX the DA increases were higher and lasted longer than those observed in animals microinjected with PBS.…”
Section: Discussionmentioning
confidence: 99%